2012
DOI: 10.4028/www.scientific.net/kem.504-506.1117
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Temperature, Strain Rate and Strain on the Induced Mechanical Properties of Biaxially Stretched PET

Abstract: The study is focused on the effect of strain rate, temperature and stretch ratio on the room temperature mechanical properties of PET (Polyethylene terephthalate) following biaxial deformation. Specimens were biaxially stretched within a temperature range 80-110°C, a strain rate in the range 1-16/s and stretch ratio in the range 1-2.8. The tensile moduli of the stretched specimens were obtained using tensile testing. Results show that post-stretching room temperature modulus increases with decreasing temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…The lower stress response was from the test with the higher heating temperature. However the gradient of the strain hardening region is less diverse when compared with the data typically generated from biaxial stretching tests [9][11], even when comparing a similar temperature range from 91℃ to 105℃. The cause of this observation is due to the deformation of the material being driven by the internal pressure during the blowing instead of being controlled by the imposed displacement profile in the biaxial stretching test, i.e.…”
Section: Figure 11 (B) and (D)mentioning
confidence: 99%
See 1 more Smart Citation
“…The lower stress response was from the test with the higher heating temperature. However the gradient of the strain hardening region is less diverse when compared with the data typically generated from biaxial stretching tests [9][11], even when comparing a similar temperature range from 91℃ to 105℃. The cause of this observation is due to the deformation of the material being driven by the internal pressure during the blowing instead of being controlled by the imposed displacement profile in the biaxial stretching test, i.e.…”
Section: Figure 11 (B) and (D)mentioning
confidence: 99%
“…Numerous researchers world-wide have developed their own test platforms and enabled significant advances to be made in understanding the evolution of microstructure in PET materials under processing conditions [3][4][5][6][7][8][9], and to generate stress strain data that is suitable for developing and validating constitutive material laws [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Each part of the constitutive model was represented by complex equations that required a large amount of data to perform accurate curve fitting procedures. The material data used for the curve fitting procedure, and as a result the material constants, were determined from extensive material testing using the QUB biaxial stretcher [19,20] and strain history form the DIC analysis of the FSB trials. The biaxial testing was performed on 76x76x0.5mm samples of PET cut from extruded sheet, the same grade as the preform material.…”
Section: Free-blow Simulation Set-upmentioning
confidence: 99%
“…The material characterisation technique using the biaxial stretching machine was not able to replicate the sequential deformation type for every foreseeable stretch scenario; indeed, only constant width and pure biaxial deformation were captured. The amount of initial linear stretch, and therefore the onset of orientation and eventual strain hardening [19][20][21][22][23][24][25][26][27][28][29], significantly affects the inflation of the preform.…”
Section: Free-blow Analysismentioning
confidence: 99%
“…The experimental results available in Lebaudy et al (1995), Schmidt et al (2003) and Monteix et al (2001) were also used to validate numerical simulations. Recently, Salomeia et al (2013) and Menary (2012) did the first temperature measurements of the air blown inside the bottle. They showed that the temperature of the air increases as soon as the preform is introduced in the mold, before the beginning of the preblow.…”
Section: Introductionmentioning
confidence: 99%